2012
DOI: 10.4172/1948-5956.s5-004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MTDH/AEG-1 and HOTAIR Expression with Metastasis and Response to Treatment in Sarcoma Patients

Abstract: Background-Chemoresistance and metastasis are the main reasons for the failure of current treatments with sarcoma patients. Novel biomarkers are required to predict metastasis and response to treatment. The oncogene MTDH/AEG1 and the long noncoding RNA (lincRNA) HOTAIR are two novel factors involved in drug resistance and metastasis in various types of solid tumors. However, the correlation between MTDH/AEG-1 and HOTAIR expression with metastasis and drug resistance in sarcoma is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…Additionally, breast cancer patients with high HOTAIR expression had a poorer prognosis for overall survival and for metastasis-free survival than did those with low HOTAIR expression (6)(7)(8). Similar phenomena have been observed in other cancer types, such as hepatocellular carcinoma (9-11), colorectal cancer (12), sarcoma (13), gastrointestinal stromal tumors (14), pancreatic cancer (15), laryngeal squamous cell carcinoma (16), nasopharyngeal carcinoma (17), lung cancer (18,19), ESCC (20)(21)(22), gastric cancer (23,24) and melanoma (25). All these evidences indicate that lncRNA HOTAIR can act as an oncogene and increased HOTAIR expression might result in malignant transformation of normal cells.…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, breast cancer patients with high HOTAIR expression had a poorer prognosis for overall survival and for metastasis-free survival than did those with low HOTAIR expression (6)(7)(8). Similar phenomena have been observed in other cancer types, such as hepatocellular carcinoma (9-11), colorectal cancer (12), sarcoma (13), gastrointestinal stromal tumors (14), pancreatic cancer (15), laryngeal squamous cell carcinoma (16), nasopharyngeal carcinoma (17), lung cancer (18,19), ESCC (20)(21)(22), gastric cancer (23,24) and melanoma (25). All these evidences indicate that lncRNA HOTAIR can act as an oncogene and increased HOTAIR expression might result in malignant transformation of normal cells.…”
Section: Discussionsupporting
confidence: 68%
“…7,[19][20][21][22] However, the role of lncRNA-HOTAIR in the chemoresistance of SCLC remains unknown. In this study, we initially identified lncRNA-HOTAIR as a regulator in chemoresistance of SCLC by qRT-PCR in H69/H69AR and H446/H446AR cells.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature implicates MTDH as a specific mediator of lung metastasis in breast adenocarcinoma, 34 a provocative finding in light of the frequent lung metastasis among the CIC-DUX sarcomas (and, for that matter, among Ewing sarcomas). Expression of MTDH has been recently noted as a poor prognostic factor in Ewing sarcoma and other sarcomas, 35,36 and proposed as a targetable cell surface marker. 37 In contrast, we found that expression of p21 was significantly greater in CIC-DUX sarcomas.…”
Section: Discussionmentioning
confidence: 99%